2013
DOI: 10.4187/respcare.02176
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting CPAP Acceptance in Elderly Patients With Obstructive Sleep Apnea in Taiwan

Abstract: BACKGROUND: The prevalence of obstructive sleep apnea (OSA) increases with age. Treatment often includes CPAP. CPAP adherence is correlated with disease severity and symptoms. We hypothesized that CPAP acceptance rates in elderly patients with OSA would be lower than in younger patients with OSA, and examined factors associated with CPAP acceptance. METHODS: We reviewed the charts of 315 subjects with OSA (apnea-hypopnea index > 5 events/h) who were treated at our hospital from 2008 to 2011 with CPAP therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
3
28
3
Order By: Relevance
“…Consequently, it is unclear whether patients with OSA who received long-term CPAP had lower risk of RA compared to patients with similar severity of OSA but with short-term CPAP use. Yang et al 48 had reported that the rate of CPAP adherence in Taiwan is 64%, which is similar to rates reported in previous studies. [49][50][51] However, it is still possible that some patients receiving CPAP treatment were nonadherent and this would suggest that we underestimated the benefits of CPAP.…”
Section: 9-11supporting
confidence: 80%
“…Consequently, it is unclear whether patients with OSA who received long-term CPAP had lower risk of RA compared to patients with similar severity of OSA but with short-term CPAP use. Yang et al 48 had reported that the rate of CPAP adherence in Taiwan is 64%, which is similar to rates reported in previous studies. [49][50][51] However, it is still possible that some patients receiving CPAP treatment were nonadherent and this would suggest that we underestimated the benefits of CPAP.…”
Section: 9-11supporting
confidence: 80%
“…Other studies suggested a greater concern with CPAP acceptance. One study on a Chinese population reported one-third of OSA patients who declined CPAP therapy after CPAP titration 10 while another study performed in Taiwan reported an even lower CPAP acceptance rate of 39.7%, particularly among the elderly 11 . Predictors of CPAP adherence which are largely based on studies conducted in the Western population may be broadly classified into factors including disease and patient characteristics, treatment titration procedures, device factors, psychological and social factors 12 .…”
Section: Introductionmentioning
confidence: 99%
“…This was also documented in our previous study. 15 This interesting result showing that subjects in the low-adherence group were younger reveals that savvy and health concern seem more common in older subjects. We claim that this is also possibly related to socioeconomic status.…”
Section: Cpap Acceptance In Subjects Of Different Agesmentioning
confidence: 76%